Interdependent Expression of the ccoNOQP-rdxBHIS Loci in Rhodobacter sphaeroides 2.4.1 - Roh, Jung Hyeob (American Society for Microbiology, 2002)
The rdxBHIS gene cluster of Rhodobacter sphaeroides 2.4.1, located downstream of the ccoNOQP operon encoding the cbb(3) cytochrome c oxidase, is required for the posttranscriptional modification of the cbb(3) cytochrome c oxidase. The cbb(3) cytochrome c oxidase is the main terminal oxidase under microaerobic conditions, as well as a component of the signal transduction pathway controlling photosynthesis gene expression. Because of the intimate functional and positional relationships of the ccoNOQP operon and the rdxBHIS gene cluster, we have examined the transcriptional activities of this DNA region in order to understand their expression and regulation. Northern blot analysis and reverse transcription-PCR, together with earlier complementation analysis, suggested that the ccoNOQP-rdxBHIS cluster is transcribed as ccoNOQP-, ccoNOQP-rdxBH-, rdxBH-, and rdxIS-specific transcripts. Multiple transcriptional start sites have been identified by primer extension analyses: five for ccoN, four for rdxB, and one for rdxI. Transcription from P1(N) of ccoN and P1(B) of rdxB is dependent on the presence of FnrL. LacZ fusion analysis support the above-described studies, especially the importance of FnrL. Expression of the cco-rdx cluster is closely related to photosynthesis gene expression, suggesting that transcript stoichiometry and presumably the stoichiometry of the gene products are critical factors in controlling photosynthesis gene expression.